New Trends in Business Management. Strategy, Branding, Teamwork - Witek-Crabb, Anna. Redakcja; Radomska, Joanna. Redakcja (Debiuty studenckie. New Trends in Business Management, 2025)
[In this issue of Students Debuts: New Trends in Business Management, student authors particularly examine strategy, branding and teamwork through case studies and analytical considerations. Several articles focus on the strategic aspects of business management. One case examines Italmetal’s implementation of Lean Manufacturing, Six Sigma and digital supply-chain systems to raise equipment performance. Another traces the Wielton Group’s entry into African markets, showing how strategic sales approaches and close customer engagement drive growth. Together, these articles illustrate how strategy, brand identity and team processes evolve in a fast-moving business landscape.] z zapowiedzi
s. 220